KONSEP LANANG DAN WADON SEBAGAI SIMBOL KESETARAAN GENDER DALAM KEHIDUPAN RELIGI DAN SOSIO-KULTURAL MASYARAKAT HINDU DI DESA TRUNYAN, BANGLI - Sabda Jayendra, Putu (PANGKAJA: JURNAL AGAMA HINDU, 2018)
Hinduism and Balinese culture have become an integral whole. The identity of Hinduism with Balinese culture brings consequences, namely the negative stigma given by many people about gender equality. The Balinese Hindu community in their socio-cultural life generally adopts a patri- archal system that positions women to be subordinate of the men, which is in fact contradictory to Hindu teachings that teach equality, rights and duties. But specifically for the Hindu community in Trunyan Village, Kintamani has the concept of Lanang and Wadon as a reflection of equality of male and female aspects deeply rooted from the religious system to the foundation of the socio-cultural life. The Trunyan Village community’s understanding of the teachings of equality in Hinduism adapt- ed through the local terminology of Lanang and Wadon can be an answer to how Hindu religion teaches flexibly the principle of gender equality of men and women.